FPGAs for Trusted Cloud Computing - Eguro, Ken; Venkatesan, Ramarathnam (International Conference on Field-Programmable Logic and Applications, 2012)
FPGA manufacturers have offered devices with bitstream protection for a number of years. This feature is currently primarily used to prevent IP piracy through cloning. However, in this paper we describe how protected bitstreams can also be used to create a root of trust for the clients of cloud computing services. Unlike related software-based solutions, this hardware-based approach solves a fundamental problem that currently impedes the greater adoption of cloud computing: how to secure client data and computation from both potential external attackers and an untrusted system administrator. We examine how this approach can be applied to the specific application of handling sensitive health data. This system maintains the advantages of the cloud with minimal additional hardware. We also describe how this system can be extended to provide a more generic secure cloud architecture.